PORT COMMUNITY SYSTEMS (PCS) AND PORT PERFORMANCE - Caldeirinha, Vitor Manuel dos Ramos (2020)
This study aims to evaluate the port community system (PCS) effect and its influence in port performance. In the Portuguese case, the port single window (JUP) is evaluated, with which it is identified. It was used analysis of the main components and the structural equation modeling (SEM) methodology, applied to the sample of 153 valid responses, obtained in the Portuguese port community. The results show different factors that constitute the port community system and big differences between the generic PCS and the Portuguese PCS (JUP). The performance factors also present strong differences. As the main contribution, we verify the different factors of PCS with impact on different performance factors.